EVALUASI WAKTU TEMPUH PENGUNJUNG ELEVATOR PADA AREA WEST MALL DI GRAND INDONESIA - Kasaf, Michel; Pradita, Rahayu; Sukma Anandita, Hillary Widiyanti; Melati Nuritasandi, Dora (STKIP PGRI Situbondo, 2024)
Elevators is used as vertical transportation devices in multi-story buildings. The Grand Indonesia Mall in the West Mall area provides two areas for its elevators, one of which is the Arjuna Elevator in the foodprint area. According to the Indonesian National Standard (SNI) 03-6573-2001, in a standard building, visitors typically wait for elevators for about 40-60 seconds. However, at the Arjuna Elevator, the waiting time exceeds 60 seconds, leading to queues. The reference used in this study is SNI 03-6573-2001, and the research method involves direct survey implementation conducted over 14 days. The calculation results based on direct surveys show that the travel time of the Arjuna Elevator is 80 seconds. It is noted that only 2 out of 3 units are currently operational, with 1 unit undergoing repairs. Consequently, the average waiting time for each unit is 120.997 seconds. The capacity within 5 minutes reaches 100 people, and the circulation demand is 9.17%, while the minimum circulation demand according to SNI 03-6573-2001 is 10%. Based on these calculations, It is concluded that the optimal number of elevator units is 3, resulting in a circulation demand of 10.09% for the Arjuna Elevator in the West Mall area of Grand Indonesia.